Modeling and simulation of magnetorheological dampers for the reduction of the seismic response of structures using simulink - Guzmán Prado, Miguel Raúl (2022)
The control devices can be used to dissipate the energy of structures subjected to dynamic loads in order to reduce structural damage and prevent the failure of them. The semiactive control devices that have received great attention in recent years are magnetorheological (MR) fluid dampers due to their mechanical simplicity, high dynamic range, large temperature operating range and low power requirements. In the present research work, Matlab and Simulink are used as computational tools for the modeling and simulation of structural control systems with magnetorheological dampers (MRDs). To begin with, the modeling is carried out through simulink block diagrams of the governing differential equations of representative mathematical models of MRDs. Next, a series of simulations is performed in order to replicate experimental results and to be able to validate the modeling step. Finally, the MRDs are integrated together with a semiactive control algorithm and an idealized ten-degrees-of-freedom structure. The main expected outcome is the reduction of the seismic response (response histories, drifts, shear forces and overturning moments).